Management practices adopted by dairy farmers during milking and transportation in the Jaffna district, Sri Lanka - Susruthan, V.; Sinniah, J. (University of Ruhuna, Sri Lanka, 2021)
This study focused on investigating the milking management practices adopted by dairy farmers in four major milk collecting organizations of the Jaffna district in Sri Lanka. The study was carried out from February 2020 to July 2020. Out of 2254 farmers supplying milk to four major milk collecting organizations, 15% of the farmers were randomly selected for the current study. Information from the selected farmers was gathered using a structured questionnaire. Data were analysed using Proc frequency and Chi-Square test in SAS. The overall results revealed that the predominant method of milking method was hand milking (99%) with twice a day milking frequency (59.9%). Eighty-three percent of dairy farmers used metal containers to transport milk. 58.4% of the farmers relied on dug well as a source of water for dairying activities. 12.4% of dairy farmers faced water shortage problem for dairying. Ninety-three percent of the farmers cleaned the milk yard before milking. Mainstream of dairy farmers (79%) filtered milk before delivering to the collection points, where they mostly used metal containers (83%) and plastic filters (83%). Most of dairy farmers (99-100%) washed their hands, utensils, and udder before milking. 72% of milk producers practiced drying udder after wash; out of them majority (94.6%) used cloths as drying material. The majority of the farmers allowed the calf to suck the milk before milking (92%), monitored animal health before milking (95%), and delivered the milk to the collection point within one hour of milk collection (99%). The differences among collection organizations were significant for type of containers, shortage of water, schedule of cleaning the yard, frequency of milking, filtering the milk, filter material, allowing calves to suckle before milking and cow health monitoring. The differences among collection organizations were not significant for the method of milking, source of water, washing of hands and pails before milking, washing the udder before milking, drying of udder after wash, udder drying material, and transport time to collection centres. The study revealed that there is room for improvement in the hygienic practices adopted by the farmers in the study area. Educating dairy farmers regarding the appropriate hygienic management practices will enhance clean milk production.
Keywords: Jaffna district; Management practices; Milk collecting organizations; Raw milk